2020
DOI: 10.3389/fneur.2020.00772
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine for Traumatic Brain Injury: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Limitations

Abstract: Background: This systematic review aimed to evaluate the effectiveness (functional outcomes and clinical symptoms) and safety (incidence of adverse events) of herbal medicine (HM) as monotherapy or adjunctive therapy to conventional treatment (CT) for traumatic brain injury (TBI). Methods: We comprehensively searched 14 databases from their inception until July 2019. Randomized controlled trials (RCTs) using HM as monotherapy or adjunctive therapy to treat TBI patients were included. The primary outcome was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Mechanical and chemical stimulation could be sought simultaneously during the procedure [ 40 ], and it also has an excellent safety record [ 41 ], resulting in its use as a treatment modality for various musculoskeletal disorders. In addition, previous studies have reported on the effectiveness of herbal therapy in treating neck pain [ 42 ], traumatic brain injury [ 43 ] and pain caused by blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and chemical stimulation could be sought simultaneously during the procedure [ 40 ], and it also has an excellent safety record [ 41 ], resulting in its use as a treatment modality for various musculoskeletal disorders. In addition, previous studies have reported on the effectiveness of herbal therapy in treating neck pain [ 42 ], traumatic brain injury [ 43 ] and pain caused by blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is possible that regulating aquaporins could lead to improvements in peritumoral edema. Goreisan, a herbal medicine used in Japan and other Asian countries (known as Wu Ling San in China and Oreongsan in Korea), is considered to inhibit edema through downregulating aquaporin 4 expression [96][97][98][99]. Studies have demonstrated its efficacy in reducing cerebral edema following stroke [100].…”
Section: Aquaporin Inhibitorsmentioning
confidence: 99%
“…[5] Cognitive symptoms are an especially common and important area of concern for TBI survivors, with a majority of individuals with moderate-to-severe TBI having persistent and marked cognitive impairment (IC) at 1 to 5 years post-injury. [6,7] Cognitive symptoms include deficits in attention, executive functioning, memory (encoding and retrieval), language, visuoperceptual functioning, and psychomotor functioning abilities. [8][9][10] Cognitive deficits can significantly impair activities of daily living (ADL), employment, social relationships, recreation, and active participation in the community.…”
Section: Description Of the Conditionmentioning
confidence: 99%